Perbandingan Pengetahuan dan Sikap Ibu Hamil tentang Relaksasi Aromaterapi Kopi terhadap Penurunan Tingkat Nyeri Persalinan di PMB Y Kabupaten Bandung - Risyanti, Berty (Sehat MasadaJurnal, 2021)
Pregnant women who experience excessive anxiety during pregnancy until before delivery will lead to stress that can cause pain during delivery, and this must be overcome by pregnant women who must have calm so that the labor process becomes smooth without hindrance. The calm needed can be helped by using aromatherapy relaxation such as coffee, by doing aromatherapy relaxation, it is hoped that fear, panic, tension and other pressures that haunt pregnant women in labor can be reduced or even lost so that the labor process can run normally. To overcome this problem must go through a holistic individual approach that affects the mind, body and emotion of pregnant women. So it is necessary to increase the knowledge, attitudes and behavior of pregnant women about relaxation of coffee aromatherapy so that there is a decrease in the level of labor pain. A total of 30 pregnant women who met the inclusion criteria, namely pregnant women with gestational age ? 22 weeks - 36 weeks who have participated in the class of pregnant women for at least 3 meetings, given coffee aromatherapy during the class for pregnant women, following the research during January 2019 - March 2019. Sampling using consecutive sampling technique. This study used a pre-experimental design with one group pretest-posttest design technique. The results showed that the average value of knowledge before treatment was 11.43 and after treatment was 14.94. The average value of the attitude before being given treatment was 49.31 and after treatment was 65.54, and there was an effect of attending the class of pregnant women to increase the knowledge and attitudes of pregnant women in the use of coffee aromatherapy (p = 0.001) with an average knowledge of 3.514. and the average attitude is 16,229. Based on the results of the study, it can be concluded that there is an effect of the class of pregnant women on increasing the knowledge and attitudes of mothers about relaxing coffee aromatherapy on reducing the level of labor pain.